2018
DOI: 10.1111/cas.13829
|View full text |Cite
|
Sign up to set email alerts
|

FBXW7 modulates malignant potential and cisplatin‐induced apoptosis in cholangiocarcinoma through NOTCH1 and MCL1

Abstract: The ubiquitin ligase F‐box and WD repeat domain‐containing 7 (FBXW7) is responsible for degrading diverse oncoproteins and is considered a tumor suppressor in many human cancers. Inhibiting FBXW7 enhances the malignant potential of several cancers. In this study, we aimed to investigate the role of FBXW7 in cholangiocarcinoma. We found that FBXW7 expression was associated with clinicopathological outcomes in cholangiocarcinoma patients. Both disease‐free and overall survival were significantly worse in the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Recently studies have suggested that aberrant activation of the Notch signaling accelerates cell proliferation in endometrial cancer, and suppression of mTOR signaling pathway in EC inhibits tumor initiation and progression [45,46]. Mori et al demonstrated that FBXW7 modulates cell apoptosis via inhibiting Notch signaling pathway [47]. Our results also showed that over-expressing FBXW7 suppressed Notch signaling related protein and p-mTOR/mTOR, and regulated the proliferation and apoptosis of EC cells through Notch/mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 71%
“…Recently studies have suggested that aberrant activation of the Notch signaling accelerates cell proliferation in endometrial cancer, and suppression of mTOR signaling pathway in EC inhibits tumor initiation and progression [45,46]. Mori et al demonstrated that FBXW7 modulates cell apoptosis via inhibiting Notch signaling pathway [47]. Our results also showed that over-expressing FBXW7 suppressed Notch signaling related protein and p-mTOR/mTOR, and regulated the proliferation and apoptosis of EC cells through Notch/mTOR signaling pathway.…”
Section: Discussionsupporting
confidence: 71%
“…As a member of the F-box protein family, FBXW7 is an important tumor-suppressor gene and one of the most-commonly deregulated ubiquitin-proteasome system proteins in human cancers [12]. The degradation of oncoproteins, such as cyclin E, c-Myc, Mcl-1, mTOR, Jun, Notch, and AURKA, can be regulated by FBXW7 [29,30]. As a frequently-mutated gene in cancers, we identified that FBXW7 was downregulated in HCC specimens compared with that of normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, FBXW7 restrains the epithelial-to-mesenchymal transition (EMT) process in non-small-cell lung cancer (30). FBXW7 inhibits cholangiocarcinoma progression via NOTCH1 and MCL1 (31). In the present study, the FBXW7 gene was shown to be a downstream target gene of miR-5000-3p in laryngocarcinoma.…”
Section: Discussionmentioning
confidence: 55%